Answer:
The initial value problem ![y(x) = 4 e^{-2x} -3 e^{6 x}](https://tex.z-dn.net/?f=y%28x%29%20%3D%204%20e%5E%7B-2x%7D%20-3%20e%5E%7B6%20x%7D)
Step-by-step explanation:
<u>Step1:</u>-
a) Given second order homogenous constant co-efficient equation
![y^{ll} - 4y^{l}-12y=0](https://tex.z-dn.net/?f=y%5E%7Bll%7D%20-%204y%5E%7Bl%7D-12y%3D0)
Given equation in the operator form is ![(D^{2} -4D-12)y=0](https://tex.z-dn.net/?f=%28D%5E%7B2%7D%20-4D-12%29y%3D0)
<u>Step 2</u>:-
b) Let f(D) = ![(D^{2} -4D-12)y](https://tex.z-dn.net/?f=%28D%5E%7B2%7D%20-4D-12%29y)
Then the auxiliary equation is ![(m^{2} -4m-12)=0](https://tex.z-dn.net/?f=%28m%5E%7B2%7D%20-4m-12%29%3D0)
Find the factors of the auxiliary equation is
![m^{2} -6m+2m-12=0](https://tex.z-dn.net/?f=m%5E%7B2%7D%20-6m%2B2m-12%3D0)
m(m-6) + 2(m-6) =0
m+2 =0 and m-6=0
m=-2 and m=6
The roots are real and different
The general solution ![y = c_{1} e^{-m_{1} x} + c_{2} e^{m_{2} x}](https://tex.z-dn.net/?f=y%20%3D%20c_%7B1%7D%20e%5E%7B-m_%7B1%7D%20x%7D%20%2B%20c_%7B2%7D%20e%5E%7Bm_%7B2%7D%20x%7D)
the roots are ![m_{1} = -2 and m_{2} = 6](https://tex.z-dn.net/?f=m_%7B1%7D%20%3D%20-2%20and%20m_%7B2%7D%20%3D%206)
The general solution of given differential equation is
![y = c_{1} e^{-2x} + c_{2} e^{6 x}](https://tex.z-dn.net/?f=y%20%3D%20c_%7B1%7D%20e%5E%7B-2x%7D%20%2B%20c_%7B2%7D%20e%5E%7B6%20x%7D)
<u>Step 3</u>:-
C) Given initial conditions are y(0) =1 and y1 (0) =-26
The general solution of given differential equation is
.....(1)
substitute x =0 and y(0) =1
![y(0) = c_{1} e^{0} + c_{2} e^{0}](https://tex.z-dn.net/?f=y%280%29%20%3D%20c_%7B1%7D%20e%5E%7B0%7D%20%2B%20c_%7B2%7D%20e%5E%7B0%7D)
.........(2)
Differentiating equation (1) with respective to 'x'
![y^l(x) = -2c_{1} e^{-2x} + 6c_{2} e^{6 x}](https://tex.z-dn.net/?f=y%5El%28x%29%20%3D%20-2c_%7B1%7D%20e%5E%7B-2x%7D%20%2B%206c_%7B2%7D%20e%5E%7B6%20x%7D)
substitute x= o and y1 (0) =-26
![-26 = -2c_{1} e^{0} + 6c_{2} e^{0}](https://tex.z-dn.net/?f=-26%20%3D%20-2c_%7B1%7D%20e%5E%7B0%7D%20%2B%206c_%7B2%7D%20e%5E%7B0%7D)
.............(3)
solving (2) and (3) by using substitution method
in equation (3)
![-2c_{1} + 6(1-c_{1}) = -26](https://tex.z-dn.net/?f=-2c_%7B1%7D%20%2B%206%281-c_%7B1%7D%29%20%3D%20-26)
on simplification , we get
![-2c_{1} + 6(1)-6c_{1}) = -26](https://tex.z-dn.net/?f=-2c_%7B1%7D%20%2B%206%281%29-6c_%7B1%7D%29%20%3D%20-26)
![-8c_{1} = -32](https://tex.z-dn.net/?f=-8c_%7B1%7D%20%3D%20-32)
dividing by'8' we get ![c_{1} =4](https://tex.z-dn.net/?f=c_%7B1%7D%20%3D4)
substitute
in equation ![1 = c_{1} + c_{2}](https://tex.z-dn.net/?f=1%20%3D%20c_%7B1%7D%20%20%2B%20c_%7B2%7D)
so ![c_{2} = 1-4 = -3](https://tex.z-dn.net/?f=c_%7B2%7D%20%3D%201-4%20%3D%20-3)
now substitute
in general solution
![y(x) = c_{1} e^{-2x} + c_{2} e^{6 x}](https://tex.z-dn.net/?f=y%28x%29%20%3D%20c_%7B1%7D%20e%5E%7B-2x%7D%20%2B%20c_%7B2%7D%20e%5E%7B6%20x%7D)
![y(x) = 4 e^{-2x} -3 e^{6 x}](https://tex.z-dn.net/?f=y%28x%29%20%3D%204%20e%5E%7B-2x%7D%20-3%20e%5E%7B6%20x%7D)
now the initial value problem
![y(x) = 4 e^{-2x} -3 e^{6 x}](https://tex.z-dn.net/?f=y%28x%29%20%3D%204%20e%5E%7B-2x%7D%20-3%20e%5E%7B6%20x%7D)